Presentation of Islamic Believes in Textual Formation of Urdu Dastan ‘Bagh o Bahar’: اُردوداستان ”باغ و بہار“ کی متنی تشکیل : اسلامی عقائد کی پیش کش - Ijaz, Dr. Sumaira (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
The tradition of Urdu Dastan writing was started in 17th century and in 19th century it reached at its apex. Bagh o Bahar, written by Meer Amman is the prominent dastan of 19th century which effectively presents the Islamic beliefs, reflected in culture, social structure, religious values and behaviors of the characters. So, this dastan becomes the source of knowing the Islamic beliefs of nineteenth century. This article is actually the close textual study which indicates the Islamic beliefs presented in this dastan.